MnO2 and TiO2 Catalyzed the Hydrolysis of Quinalphos - Esbata A1*, Buncel E2, W. vanLoon G2 (AlQalam Journal of Medical and Applied Sciences, 2017)
Hydrolysis of the organophosphorothioate ester, quinalphos (Q, O,O-diethyl O-quinoxaline-2-yl phosphorothioate) was investigated in the absence and presence of either MnO2 or TiO2 (heterogeneous catalysis) at 25oC and pH 4.0, 7.0, and 10.0. The hydrolysis products were 2-hydroxyquinoxaline (HQ) and O,O-diethyl phosphorothioic acid (PA). Hydrolysis of quinalphos was studied by determining the disappearance of Q as well as appearance of HQ product using HPLC with UV detection. At these pH values, MnO2 was found to exert a significant catalytic effect. TiO2 also facilitated the hydrolysis of Q, but only to a small extent..